Nationalism: A Theoretical Approach - Çınar, Selin (Historia i Polityka, 2023)
The origin of the first research on the definition of nationalism dates back to the 18th century. Thus, the formation of the concept of nationalism was influenced by the Industrial Revolution, and then the concept continued to develop until today. The aim of the article is to explain the basic arguments of modernist nationalism theories and their shortcomings.